Materi Dakwah Majalah Al-Munir - Sarwan Sarwan (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2012)
This literary is aimed to express the classification of Islamic preaching material of Al-Munir. Based on the research by studying directly the primary source of Al-Munir magazine published between the years 1911 to 1915, found that the material contained in the Islamic preaching magazine Al-Munir consists of the form of articles, correspondence, news and advertising.